A study on stress management in HDFC bank in Chennai - CHERUKUR, MR. RAMBABU; SHERLIN S N, Ms. JOHANNA SWEETY (The journal of contemporary issues in business and government, 2020)
The purpose of the study is to know about the stress management in HDFC Bank. The study focuses on knowing the stress level in the banking sector particularly in HDFC bank. In recent times the employees in the banking sector are facing stress, depression, sleeping disturbance, etc. This is due to inability of employees to cope up with the updating technology, trends and strategies in the banking sector. The emerging new technologies and over use of computers leads to stress for the employees. Not only the wellbeing also the physical wellbeing is affected due to stress. This is an empirical study with descriptive research methodology. Surveys were taken through questionnaires. Totally sixty responses were collected from the employees of HDFC bank. The questionnaire contains nine questions that measure the employee involvement and stress overcome strategies. The software used in this study is SPSS software. The analytical tools used to measure the demographic variables are frequency analysis and the mainstream that relates the research that is analysed by mean analysis, t-test and one way anova test. This research finally concludes that banking sector employees are undergoing stress due to that they are not willing to leave the job instead they are trying to overcome stress with different strategies.